Effect of Anti Phospholipid Antibodies on in vitro fertilization/intracytoplsmic sperm injection outcome - Elham Azimi Nekoo; Ensieh Shahrokh Tehrani Nejad; Batool Rashidi; Hossein Kilani; Habib Moazami Goudarzi (Tehran University of Medical Sciences, 2007)
Objective: The study aimed to determine the relationship between presence of antiphospholipid antibodies (APLs) and clinical pregnancy rate in patients undergoing IVF/ICSI procedures. Materials and methods: This descriptive-analytic study performed on two hundred consecutive women referred for IVF/ICSI in Vali-e-Asr Reproductive Health Research Center. Serum levels of APLs , anticardiolipin [aCL], antiphosphatidic acid [aPA], antiphosphatidyl choline [aPC] and antiphosphatidylserine [aPS] were checked for all patients before starting IVF cycles. APLs  seropositivity and clinical pregnancy rate were determined. T-test and Mann-Whitney were used to compare two groups. P value <0.05 was considered significant. Results: 23 women (11.5%) were APL positive. Twenty nine women of 177 APL seronegative patients (16.4%) became pregnant while only one of 23 seropositive patients (4.3%) was pregnant. Clinical pregnancy rate was not significantly different in two groups. Conclusion: Although APLs were common, these antibodies did not affect the outcome of IVF/ICSI procedures. Thus screening for APLs is not recommended in women undergoing these procedures.